2022
DOI: 10.7717/peerj.14246
|View full text |Cite
|
Sign up to set email alerts
|

Level of anxiety and depression among healthcare workers in Saudi Arabia during the COVID-19 pandemic

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic places a high demand on frontline healthcare workers. Healthcare workers are at high-risk of contracting the virus and are subjected to its consequential emotional and psychological effects. This study aimed to measure the level of depression and anxiety among healthcare workers in Saudi Arabia during the early stages of the COVID-19 pandemic. Methods This was a cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Furthermore, the results are also in line with the result of a previous study on Yemen by Alrubaiee et al [ 19 ] who found similarly high levels of respondent anxiety during the battle against the COVID-19 outbreak. The results of this study differ from the results of Shamsan et al [ 34 ] and Al Ammari et al [ 35 ] from Saudi Arabia, who found that Saudi HCWs have lower levels of anxiety, depression and insomnia than were observed in Yemen. These contradictory findings could be due to the differences in settings of the studies, availability of PPE, and the diversity of the respondents who participated in the study.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the results are also in line with the result of a previous study on Yemen by Alrubaiee et al [ 19 ] who found similarly high levels of respondent anxiety during the battle against the COVID-19 outbreak. The results of this study differ from the results of Shamsan et al [ 34 ] and Al Ammari et al [ 35 ] from Saudi Arabia, who found that Saudi HCWs have lower levels of anxiety, depression and insomnia than were observed in Yemen. These contradictory findings could be due to the differences in settings of the studies, availability of PPE, and the diversity of the respondents who participated in the study.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of disease control, they have also been subject to various techniques [13]. Other students have been hired for hospital-based roles to combat the health system saturation, while some medical schools have banned students from any patient interaction, as advised by the American Association of Medical Colleges, depriving the students of a crucial component of their curriculum [14].…”
Section: Introductionmentioning
confidence: 99%